2022
DOI: 10.1037/pha0000523
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of nicotine concentration and device power on electronic nicotine delivery system (ENDS) abuse liability among exclusive ENDS users and dual users of ENDS and combustible cigarettes.

Abstract: Open-system electronic nicotine delivery systems (ENDS) permit modifications to device characteristics such as power, potentially increasing nicotine and toxicant delivery. Limiting liquid nicotine concentration may carry unintended consequences by prompting users to increase device power to increase nicotine delivery. This study examined the abuse liability of ENDS across nicotine concentration and power settings. In a clinical laboratory study, n = 19 exclusive ENDS users and n = 13 dual ENDS/cigarette users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…This is concerning given that more toxicants are produced when a higher power is used. (Hoetger et al, 2021 Oct 14) It is also worth noting that those who smoked cigarettes in the past 30 days were less likely to use tank-like devices and more likely to use pod-type devices with a nicotine salt liquid (that have a relatively high nicotine concentration), compared to those who did not currently smoke cigarettes. This may be because people who are currently smoking cigarettes are looking for an easy way to obtain high doses of nicotine in a more simple and discreet manner; further, JUUL was starting to market their devices to adult smokers as cigarette replacements, encouraging them to "Make the Switch" (https://tobacco.stanford.edu/pods/juul/switch/).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is concerning given that more toxicants are produced when a higher power is used. (Hoetger et al, 2021 Oct 14) It is also worth noting that those who smoked cigarettes in the past 30 days were less likely to use tank-like devices and more likely to use pod-type devices with a nicotine salt liquid (that have a relatively high nicotine concentration), compared to those who did not currently smoke cigarettes. This may be because people who are currently smoking cigarettes are looking for an easy way to obtain high doses of nicotine in a more simple and discreet manner; further, JUUL was starting to market their devices to adult smokers as cigarette replacements, encouraging them to "Make the Switch" (https://tobacco.stanford.edu/pods/juul/switch/).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of nicotine and non-nicotine toxicants that an ENDS device/liquid combination can deliver has implications for how effective it can be to help people stop using cigarettes, for dependence (abuse liability), and for potential health effects. (Gades et al, 2022;Hoetger et al, 2021 Oct 14) A device's power characteristics (wattage: a function of battery voltage and heating coil resistance), nicotine concentration of the liquid, and nicotine form (salt or free-base) all influence the amount of nicotine delivered to the user. (Shihadeh and Eissenberg, 2015 Feb;El Hourani et al, 2022;Wagener et al, 2017 Mar;Leventhal et al, 2021 Jan 4;Talih et al, 2021;Talih et al, 2020 Oct 1;Hiler et al, 2020 Oct) Which products are being used and by whom has implications for understanding how ENDS use benefits or harms individual and public health.…”
Section: Introductionmentioning
confidence: 99%
“…planned sample size was based on power analyses for outcomes not related to these analyses (Hoetger et al, 2021). Eligibility required a semiquantitative urine cotinine result of "positive" at screening (≥200 ng/mL; urine cotinine cassette test).…”
Section: Methods Samplementioning
confidence: 99%
“…The "mLs of liquid" price-framed task was identical to the puffs-version, but specified mLs of e-cigarette liquid rather than 10 puffs. Counterbalancing the order the purchase tasks was impractical because of other design elements of the study reported elsewhere (Hoetger et al, 2021), thus the puffs-version of the E-CPT was always administered first followed immediately by the mL-version. Both E-CPTs were computer administered and displayed the total number of 10-puff bouts or mLs of liquid purchased, as well as the associated expenditure, for each price-point prior to participants confirming their purchases.…”
Section: Study Design and Materialsmentioning
confidence: 99%
“…The factors shaping substance use progression among young people are complex and often warrant the consideration of multiple theoretical frameworks [ 18 ]. To examine predictors of e-cigarette use discontinuation, the present study considered variables central to social cognitive, dispositional, and affective models of substance use etiology [ 18 ] and factors implicated in increase of e-cigarette use dependence and abuse liability [ 19 , 20 ]. Dispositional variables such as sensation seeking have been strongly related to tobacco use progression [ 21 ].…”
Section: Introductionmentioning
confidence: 99%